Prosody-focused feedback enhances the efficacy of anti-depressive self-statements in depressed individuals – A randomized controlled trial - Bauer, Jonathan; Schindler-Gmelch, Lena; Gerczuk, Maurice; Schuller, Björn; Berking, Matthias (Behaviour Research and Therapy, 2025)
This study was aimed to evaluate whether the efficacy of invoking anti-depressive self-statements to cope with depressed mood can be enhanced for depressed individuals by systematically guiding them to amplify the expression of conviction in their voice. Accordingly, we recruited N = 144 participants (48 clinically depressed individuals, 48 sub-clinically depressed individuals, and 48 non-depressed individuals). Participants were randomly assigned to an experimental or control condition. Across study conditions, participants completed a mood induction procedure, then read aloud scripted anti-depressive self-statements designed to reduce depressed mood. Participants in the experimental condition received instructions to heighten the prosodic expression of conviction in their voice; participants in the control condition received no prosodic expression instructions. Results showed that depressed participants achieved a more pronounced decrease of depressed mood in the experimental condition than in the control condition. Further, the results indicated no effects in sub-clinically depressed and non-depressed individuals. Finally, heightened conviction expressed by participants in the experimental condition was associated with lower depressed mood and diminished depressive symptom severity. Overall, our findings suggest that fostering the prosodic expression of conviction in depressed persons’ voices, while they vocalize anti-depressive self-statements, represents a promising method for augmenting the efficacy of cognitive interventions for depressio
CRIS-Team Scopus Importer:2025-02-17
Keywords: Major depressive disorder; Cognitive restructuring; Prosody; Voice; Interacting cognitive subsystems; Embodiment